(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The content and the role of the methodological system, which provides for close interaction of higher educational institutions and enterprises of the country’s industry sectors are considered in the process of training modern innovative professionally-oriented graduates with creative thinking, capable of creating innovations and implementing them into the real sector of the economy The education system of the republic is aimed at ensuring high quality level of graduates. The determining content and quality of such training in the education system are innovative processes: complex, mutually influencing and mutually enriching processes. The choice of an innovation-oriented development path contributes to the provision of the education system with a high quality of training of specialists and an increase in the integration level of the market of educational services into the labor market by attracting faculty and students to the innovative activities of the republic’s economy sectors. This will make it possible to orient the modern system of higher education towards a science-intensive, practically directed system of training and retraining of specialists [1].